Methylation of MYLK3 gene promoter region: a biomarker to stratify surgical care in ovarian cancer in a multicentre study - Phelps, David L (Br J Cancer, 2017)
BACKGROUND: Survival benefit from surgical debulking of ovarian cancer (OC) is well established, but some women, despite total macroscopic clearance of disease, still have poor prognosis. We aimed to identify biomarkers to predict benefit from conventional surgery. METHODS: Clinical data from women debulked for high-stage OC were analysed (Hammersmith Hospital, London, UK; 2001–2014). Infinium’s HumanMethylation27 array interrogated tumour DNA for differentially methylated CpG sites, correlated to survival, in patients with the least residual disease (RD; Hammersmith Array). Validation was performed using bisulphite pyrosequencing (Charité Hospital, Berlin, Germany cohort) and The Cancer Genome Atlas’ (TCGA) methylation data set. Kaplan–Meier curves and Cox models tested survival. RESULTS: Altogether 803 women with serous OC were studied. No RD was associated with significantly improved overall survival (OS; hazard ratio (HR) 1.25, 95% CI 1.06–1.47; P=0.0076) and progression-free survival (PFS; HR 1.23, 95% CI 1.05–1.43; P=0.012; Hammersmith database n=430). Differentially methylated loci within FGF4, FGF21, MYLK2, MYLK3, MYL7, and ITGAE associated with survival. Patients with the least RD had significantly better OS with higher methylation of MYLK3 (Hammersmith (HR 0.51, 95% CI 0.31–0.84; P=0.01), Charité (HR 0.46, 95% CI 0.21–1.01; P=0.05), and TCGA (HR 0.64, 95% CI 0.44–0.93; P=0.02)). CONCLUSIONS: MYLK3 methylation is associated with improved OS in patients with the least RD, which could potentially be used to determine response to surgery.